The contralateral organization of the human nervous system as a quantum unfolded, holographic-like, artifactual representation of the underlying dynamics of a fundamentally two-dimensional universe - Zukauskis, Ronald L. (Frontiers in Systems Neuroscience, 2023)
Abstract A working hypothesis is put forward in this article that the contralateral organization of the human nervous system functions like a holographic operation by inverting and reversing quantum enfolded visual and non-visual spatial information so as to unfold it for what we experience in three dimensions. Various research observations reported elsewhere are reviewed and interpreted here as they may be related in a process that is fundamental to the contralateral organization. The basic holographic method and characteristics of image formation contained by a holograph are described as they relate to the working hypothesis. The double-slit experiment is described and its relevance to the working hypothesis.